Penegakan Klausula Non Kompetisi Di Indonesia - Suryadinata, Levy Yuda (Tribuere, 2022)
The legality of non-competition clauses, contained in employment contracts or employee regulations in Indonesia, is often disputed because it raises differences of opinion as to whether they meet the conditions for a contract to become valid, or not. In fact, rapid technological advances require companies to continue to develop their own products and compete with each other. In the end, these companies are reluctant to open up the possibility of a leak of trade secrets to their competitors, which could have occurred through the transfer of the company's workforce. Therefore, it has become customary to apply a non-competition clause to employment contracts that restricts the room of the worker to find such a job after the end of his or her period of work in a company. The question is whether the non-competition clause qualifies for the validity of an agreement under the Code of Private Law and whether a judge's judgment that states otherwise can be deemed to have been appropriate. So this article aims to answer the question, namely, whether the view of the Code of Civil Procedure Law from the alliance side on the application of non-competition clauses contained in the employment agreement, for example the East West labour agreement and the consideration of the Judge of the State Court of Cilacap in the decision of the case No. 27/PDT.G/2015/PN CLP is in accordance with the provisions of the Book of Civil Law.